PENGARUH IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KEUANGAN DAERAH (SIMDA), KUALITAS SUMBER DAYA MANUSIA, DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP KUALITAS LAPORAN KEUANGAN - Sinta Puspitaningrum; Mahirun Mahirun (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
This study aims to test and analyze whether SIMDA Implementation, Quality of Human Resources, and Top Management Support affect the Quality of Financial Reports at the Ulujami District Office. The population in this study is Ulujami District Office Employees. With a sample of 30 respondents. The type of data used in this study is primary data, namely by using a direct questionnaire instrument, which was analyzed using multiple linear regression using the SPSS program. The results of the study concluded thatThe implementation of SIMDA has a positive and significant effect on the Quality of Financial Reports, where the t value is 1.281 and the sig value. 0.037 < 0.05, The quality of Human Resources has a significant positive effect on the Quality of Financial Statements, where the t value is 2.682 and the sig value. 0.013 < 0.05, and. Top Management Support has an insignificant negative effect on the Quality of Financial Statements where t count is -1.227 and the value of sig. of 0.231> 0.05 .